2006
DOI: 10.1128/mcb.26.1.169-181.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Human Zinc Finger Proteins That Bind Methylated DNA and Repress Transcription

Abstract: In vertebrates, densely methylated DNA is associated with inactive transcription. Actors in this process include proteins of the MBD family that can recognize methylated CpGs and repress transcription. Kaiso, a structurally unrelated protein, has also been shown to bind methylated CGCGs through its three Krüppel-like C 2 H 2 zinc fingers. The human genome contains two uncharacterized proteins, ZBTB4 and ZBTB38, that contain Kaiso-like zinc fingers. We report that ZBTB4 and ZBTB38 bind methylated DNA in vitro a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
259
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(271 citation statements)
references
References 47 publications
7
259
0
5
Order By: Relevance
“…For this, we tagged proteins with the green fluorescent protein (GFP) or the red fluorescent protein (RFP). As reported, we found GFP-HIPK2 in nuclear foci (Rinaldo et al, 2008), and ZBTB4-RFP was diffuse nuclear (Filion et al, 2006b). When GFP-HIPK2 and RFP-ZBTB4 were cotransfected, there was a strong colocalization.…”
Section: Identification Of Hipk2 As a Zbtb4 Interactorsupporting
confidence: 84%
See 2 more Smart Citations
“…For this, we tagged proteins with the green fluorescent protein (GFP) or the red fluorescent protein (RFP). As reported, we found GFP-HIPK2 in nuclear foci (Rinaldo et al, 2008), and ZBTB4-RFP was diffuse nuclear (Filion et al, 2006b). When GFP-HIPK2 and RFP-ZBTB4 were cotransfected, there was a strong colocalization.…”
Section: Identification Of Hipk2 As a Zbtb4 Interactorsupporting
confidence: 84%
“…ZBTB4 binds methylated DNA and represses the transcription of methylated reporter genes (Filion et al, 2006b). Very little is known about the posttranslational modifications that regulate the activity of methyl-binding transcription factors (Clouaire and Stancheva, 2008).…”
Section: Hipk2 Phosphorylates and Downregulates Zbtb4mentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical tumor models, it has been shown that therapeutic targeting of RPS2 is an excellent approach for the eradication of prostate cancer [26] . ZBTB4 binds to methylated CpGs, repressing transcription of P21CIP1 and controlling the cellular response to p53 activation, thereby playing a crucial role in oncogenesis [27,28] . OGDH is a well-characterized auto-antigen in primary biliary cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Les protéines liant spécifiquement l'ADN méthylé sont l'interface entre méthylation de l'ADN et chromatine. À ce jour 3 familles sont connues : (1) la famille des protéines à MBD (methyl-binding domain) [9] ; (2) la famille de protéines à doigts de Zinc, contenant Kaiso, ZBTB4, et ZBTB38 [10] ; et (3) un groupe de deux protéines à domaine SRA (SET and RING-finger associated), UHRF1 et UHRF2 [11]. Les protéines MBD, ainsi que celles apparentées à Kaiso, sont des répresseurs transcriptionnels.…”
Section: La Méthylation De L'adn Ses Acteurs Et Ses Interprètesunclassified